Исследование природы и параметров колебательного процесса в технологическом механизме - Сериков, Владимир Иванович (НТУ "ХПИ", 2014)
В статье описан математический аппарат, использованный для анализа параметров рабочего цикла комплекса механизмов. Сопоставление прогнозируемых параметров и полученных экспериментальным путем показало высокую достоверность полученных результатов и эквидистантность кривых, характеризующих расчетные и экспериментальные параметры. Однако на отдельных участках наблюдалось существенное отличие значений. Проведенная работа позволила выявить природу и оценить причину отличий.

In the article a mathematical tool used for analyzing the parameters of the working cycle of the complex mechanisms is described. Comparison of the predicted parameters and experimentally obtained ones showed the high reliability of the results and equidistant curves characterizing the calculated and experimental parameters. However, there was a significant difference between the levelsin some areas. The work carried out has revealed the nature and evaluate the cause of differences. Found graphicly and numeral the periods of vibrations are indeed practically identical for the different series of experiments with different initial conditions, but identical mass-inertias and zhestkostnymy parameters of mechanism. This circumstance confirms the pulled supposition out about nature of divergences of experimental and calculations information on the separate temporal areas of the explored process. It is of interest further research of process taking into account zhestkostnykh descriptions of mechanism.
Research of nature and parameters of swaying process in a technological mechanism
Keywords: механизмы; кинематическая цепь; анализ кинематики; анализ динамики; двухзвенник; mechanism kinematic chain; kinematics analysis; dynamics analysis; dvuhzvennik; structural parameters